An Investigation on the Risk Factors of Thyroid Diseases in Community Population in Hainan. (9th July 2022) - Fang, Tuanyu; Lin, Leweihua; Ou, Qianying; Lin, Lu; Zhang, Huachuan; Chen, Kaining; Quan, Huibiao; He, Yangli
Abstract : Background . In recent years, the incidence of thyroid diseases has increased significantly, which has seriously affected people's work and life. The purpose of this study was to explore the epidemiological characteristics of thyroid diseases and autoantibodies. Method . According to the principle of overall sampling, resident residents ≥18 years and who will not move within 5 years are randomly selected. A total of 2136 eligible individuals were divided into case and control groups according to whether they have thyroid disease. Finally, the impact of potential risk factors on thyroid diseases was evaluated. Results . The overall prevalence of thyroid disease was 58.3%, and there was a significant difference in the prevalence of thyroid disease between women and men ( p = 0.004). Except for the age group ≥70 years, with the increase in age, the prevalence gradually increased ( p < 0.05). Participants with positive thyroid autoantibodies (TPOAb or TgAb) had a higher prevalence than participants with negative autoantibodies. The positive rate of autoantibodies in women was higher than that in men ( p < 0.05). UIC ( p = 0.004) and free thyroid hormone (FT4) ( p = 0.001) levels of men were higher than those of women, and the TSH level of women was higher than that of men ( p = 0.002). The regression analysis showed that women, older age, and family history of thyroid disease were independent risk factors for thyroid disease. Conclusion . The prevalence of thyroid diseases in Hainan was high. Women are more susceptible to thyroid disease than men, and the prevalence increased with age.